Excavations at Redhouse, Adwick Le Street, Doncaster Bronze Age, Iron Age and Roman occupation - Preece, Tracy (Archaeopress Publishing Ltd., 2023)
From May 2000 to June 2017, MOLA (Museum of London Archaeology) undertook a programme of archaeological excavations and watching briefs at Adwick Le Street, 6.5km to the north-west of Doncaster (South Yorkshire). They revealed evidence for Bronze Age, Iron Age and Roman activity
Keywords: Vor- und Frühgeschichte; Ausgrabung; Funde; Adwick le Street; Doncaster (England) / Antiquities; Excavations (Archaeology) / England / Doncaster; Bronze age / England; Iron age / England; Doncaster (England) / Antiquities, Roman; Fouilles (Archéologie) / Angleterre / Doncaster